2009
DOI: 10.1136/vr.164.5.147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscular acepromazine and diazepam on tear production in rabbits

Abstract: Sixteen New Zealand white rabbits were divided randomly into two groups of eight. Schirmer II tear tests were performed on all 16 and then eight received an intramuscular dose of 1 mg/kg acepromazine and the other eight received an intramuscular dose of 1 mg/kg diazepam. The Schirmer tests were repeated after 15 and 25 minutes. There was a significant reduction in tear production by the rabbits treated with acepromazine, but no significant change in tear production by the rabbits treated with diazepam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…Anticholinergics have been used to inhibit or treat bradycardia during the perioperative period in veterinary medicine but are well-known to decrease tear production after systemic or topical application in dogs. 15,16 Results of the present study suggested that a combination of many drugs may induce a decrease in tear production during the perioperative period. To achieve safe anesthesia and perioperative pain control, several drugs, such as anticholinergics, phenothiazines, opioids, benzodiazepines, and α 2 -receptor agonists, are often used as premedication.…”
Section: Discussionmentioning
confidence: 58%
“…Anticholinergics have been used to inhibit or treat bradycardia during the perioperative period in veterinary medicine but are well-known to decrease tear production after systemic or topical application in dogs. 15,16 Results of the present study suggested that a combination of many drugs may induce a decrease in tear production during the perioperative period. To achieve safe anesthesia and perioperative pain control, several drugs, such as anticholinergics, phenothiazines, opioids, benzodiazepines, and α 2 -receptor agonists, are often used as premedication.…”
Section: Discussionmentioning
confidence: 58%
“…The suggested mechanism for increase in IOP after administration of certain drugs such as ketamine is because of contraction of the extraocular muscles 20 . Anesthetic and pre‐anesthetic agents are known to cause reduction in tear production 21–23 . The suggested mechanisms for tear reduction after the administration of these drugs are as follows: central effects of these drugs on autonomic regulation of tear production, effective antinociception, vasoconstriction at the tear gland itself, and altered metabolism at the gland’s cellular level 23 …”
Section: Discussionmentioning
confidence: 99%
“…20 Anesthetic and pre-anesthetic agents are known to cause reduction in tear production. [21][22][23] The suggested mechanisms for tear reduction after the administration of these drugs are as follows: central effects of these drugs on autonomic regulation of tear production, effective antinociception, vasoconstriction at the tear gland itself, and altered metabolism at the gland's cellular level. 23 However, many of the exotic animal species are not accustomed to frequent handling, and it is practically impossible to take the IOP and the STT values in unanaesthetised wild animals.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, the STT values in the paca are lower (4.10 ± 0.44 mm/min) than those previously reported in mixed‐breed rabbits ( Oryctolagus cuniculus ) (9.015 ± 3.29 mm/min) and capybaras (14.97 mm/min) . Several internal and external factors affect tear production, including interindividual variations such as age, sex, and weight as well as seasonality and the effects of drugs . Variations in the methodology, such as chemical restraint and the use of unmodified Schirmer strips, might have influenced the results obtained.…”
Section: Discussionmentioning
confidence: 56%